(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
The bioactive compounds of Gracilaria edulis were determined by using Gas Chromatography Mass spectroscopy. The drug compounds were screened for analyzing the inhibition potential against the virulent bacterial enzyme. In this research, the protein responsible for bacterial infection was docked against the drug compounds of Gracilaria edulis. The data of the virulent enzymes are studied and retrieved from PDB. The bioactive compounds were screened by Lipinski rule of five and ADMET properties. Using Autodock 4.2.6 the molecular docking analysis were done against virulent enzymes and was visualized by discovery studio 3.1. The bioactive compound eugenol with binding energy -4.42 Kcal/mol followed by 2 Heptene, 2,4,4,6 tetramethyl -3.89 Kcal/mol and 1, 2-Propanediol 2.77 Kcal/mol. The hydrogen and vanderwaals interaction of amino acids were studied. This research work mainly focuses on targeting the virulent enzymes that can reduce clinical costs by designing novel drug.